PROBLEM PENDIDIKAN MULTIKULTURAL DI INDONESIA - Hesti; Kurniansyah; Zulfadli Rizki (CV Putra Publisher, 2022)
Pluralism of ethnicity, religion, race, class, which should be the capital of development, is often manipulated by the authorities to achieve their political interests. Therefore, when conflicts break out in the region, the state seems to cover up the reality of this diversity in the name of